Proceso de atención de enfermería en adulto mayor con tumor de laringe - Vera Moreta, Mercy Gabriela (2018)
Larynx is a term that refers to the tubular organ that lies between the pharynx and the trachea. The larynx, which appears in most vertebrates, is made up of nine cartilages and is a key piece in the phonation apparatus. In humans, the larynx is located in the anterior part of the neck and borders it with the upper part of the trachea. Constituted as the organ of phonation, the larynx responds to the needs of voice and phonation by containing the upper and lower vocal cords. The invasion of a virus or bacteria, the swelling of viruses and cancer are some of the diseases that affect the larynx.